The Effect of Digital Marketing Content and Social Media Marketing on Online Buying Interest in TikTok Shop in Bandung City - Wandini Octavia Purwaningrum; Tangguh Dwi Pramono (Ebiz Prima Nusa, 2024)
The extraordinary interest of business people in the rapid spread of the Tiktok application is able to attract thousands of customers to the Tiktok Shop. The TikTok application was a phenomenon in 2018. However, the Ministry of Communication and Information Technology (Kominfo) decided to block the application because TikTok content creators often commit acts of bullying because the content is considered strange and uninformative. TikTok is popular again and the content presented is more useful, acceptable, and liked by the Indonesian people coupled with online shopping features to make it easier for users to meet their needs. Quantitative descriptive research methods with the help of statistical systems and Partial Least Square (PLS) data analysis were used to process data in this study. The results of the analysis in this study state that Digital Marketing Content and Social Media Marketing have a positive and significant influence on Purchase Intention simultaneously by 63.4%.